1.2 V Differential Difference Transconductance Amplifier and Its Application in Mixed-Mode Universal Filter - Kumngern, Montree; Suksaibul, Pichai; Khateb, Fabian; Kulej, Tomasz (My University, 2022)
This paper presents a new mixed-mode universal filter based on a differential difference transconductance amplifier (DDTA). Unlike the conventional transconductance amplifier (TA), this DDTA has both advantages of the TA and the differential difference amplifier (DDA). The proposed filter can offer four-mode operations of second-order transfer functions into a single topology, namely, voltage-mode (VM), current-mode (CM), transadmittance-mode (TAM), and transimpedance-mode (TIM) transfer functions. Each operation mode offers five standard filtering responses; therefore, at least twenty filtering transfer functions can be obtained. For the filtering transfer functions, the matching conditions for the input and passive component are absent. The natural frequency and the quality factor can be set orthogonally and electronically controlled. The performance of the proposed topology was evaluated by PSPICE simulator using the 0.18 µm CMOS technology from the Taiwan Semiconductor Manufacturing Company (TSMC). The voltage supply was 1.2 V and the power dissipation of the DDTA was 66 µW. The workability of the filter was confirmed through experimental test by DDTA-based LM13600 discrete-component integrated circuits.
Keywords: analog signal processing; differential difference transconductance amplifier; mixed-mode filter; universal filter